The Effect Intervals Using Sonic Bloom Technology On The Growth and Yield of Two Yellow Soybean Varieties - Nuraliah Nuraliah (AGRONISMA, 2022)
The aims of this study were: to determine the interaction effect of using sonic bloom technology at various time intervals on the growth and yield of two yellow soybean varieties, to determine the effect of sonic bloom exposure intervals on soybean growth and yield, and to determine differences in growth and yield of two yellow soybean varieties ( Grobogan and Dega-1). Sonic bloom technology is a technology that combines high frequency sound waves with the application of organic nutrients. High-frequency sound waves are able to stimulate the leaf mouths (stomata) to remain open so as to increase the rate and efficiency of foliar fertilizer absorption (Iriani et al., 2005). The design used is a factorial RAK which consists of two factors. The first factor is the interval of using sonic blooms consisting of three levels (interval 5 days, intervals 10 days and intervals 15 days). The second factor is the type of variety consisting of two levels V1 and V2 (Grobogan, and Dega-1). The results showed that the use of various varieties showed a good average leaf area at the age of 35, 42, 49, 63, and 70 DAP, while the use of sonic bloom technology with 5-day intervals could increase the yield of the highest number of pods at the age of 50 DAP ( 21,22). The highest fresh seed weight was (2.09 g), the highest dry seed weight was (8.82 g).